Fatores críticos de sucesso de aplicações de Business Intelligence baseadas em sistemas ERP - Sobrido, Manuel Pier (2008)
Business Intelligence (BI) is a support solution to decision-making that helps business managers turn huge volumes of transactional data into useful information, which, when timely available in the appropriate format offers support to decision making. When this technology is applied together with the ERP (Enterprise Resource Planning) system, it builds up and enhances results, since ERP forms an integrated database containing consistent data from many areas of the organization. The exploitation of this corporate database can offer valuable information, which is extremely useful to the organization decision making process. However, many companies, while implementing good BI projects from the technical viewpoint, end up not obtaining the expected results from their applications. This occurs because BI does not involve technological issues only, but also requires special attention to other important factors such as: creativity, culture and people who understands the full value of information as a strategic resource. The purpose of this study is to show the factors that should be taken into consideration, since they can make a difference between the project s success and its mediocre result. To support the reasoning of this research problem, a case study of the company PETROM Petroquímica Mogi das Cruzes S.A. was carried out. The results obtained from bibliographical research and the case study demonstrate that the critical factors for BI application success analyzed, can decisively influence the success of BI projects, especially factors dealing with the importance of executive support and BI applications alignment with company s business